The Art of Embroidery in Uzbekistan for Secondary School Students Introduction to Schools - Shomirzaev Makhmatmurad Khuramovich (Genius Publishing Group, 2023)
This article emphasizes the educational and educational value of teaching students in embroidery schools in Uzbekistan.
Keywords: embroidery; school of embroidery; principle